Performance Appraisal Model of Integrated School Principals in Disruptive Era: : A Case Study of Public High Schools in Surabaya - Mamik Suparmi; Pribadiyono; Suwitho Suwitho (International Journal of Educational Administration, Management, and Leadership, 2023)
This study aimed to develop an integrated principal performance appraisal model in the disruption era to evaluate the junior high school principal’s performance in Surabaya. The study used a research and development research design with a qualitative research approach. There were two stages undertaken namely the research stage aimed at exploring potentials and problems and analyzing the needs required in developing the appraisal model and the development stage aimed at developing a complete appraisal model along with a performance assessment tool and a performance e-report card. The performance appraisal model was developed following Sugiyono Model Level 1’s developmental research. The results of the development were in the form of a prototype model for evaluating the performance of school principals in the form of dimensions of performance targets and work behavior. The dimensions of the performance targets included the dimensions of Principal Leadership, Principal Technology Leadership, Implementation of Main Tasks, School Achievement, Personal Achievement, Civil Servant Discipline. The validation results of the performance target and work behavior instruments were valid, reliable, and very good. The developed prototype model was carried out in a limited trial on school principals, supervisors, and education experts. The result of the feasibility test for the entire principal performance appraisal prototype model was categorized very feasible and could be used to assess the performance of school principals.